2017
DOI: 10.1096/fj.201700327r
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐γ aggravates neointimal hyperplasia by inducing endoplasmic reticulum stress and apoptosis in macrophages by promoting ubiquitin‐dependent liver X receptor‐α degradation

Abstract: Neointimal hyperplasia is the main cause of restenosis after percutaneous coronary interventions (PCIs). Both IFN-γ and macrophages play nonredundant roles in the pathogenesis of vascular intimal hyperplasia; however, the underlying mechanisms remain elusive and must be further investigated. In mouse peritoneal macrophages, IFN-γ significantly accelerated degradation and up-regulated polyubiquitination of liver X receptor (LXR)-α. Signal transducer and activator of transcription 1 (STAT1) inhibitor, fludarabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…For example, Ge et al demonstrated that betaine ameliorated hepatic lipid accumulation and inflammation through restoring LXRα and PPARα expression and alleviating ER stress in fructose-fed rats—an experiment which indicated that only LXRα participated in ER stress [ 24 ]. Furthermore, Zhao et al confirmed that LXRα degradation is a key factor that induces ER stress stimulated by IFN-γ depending on the PIAS1/STAT1 pathway in macrophages [ 25 ]. However, the detailed mechanism is not fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ge et al demonstrated that betaine ameliorated hepatic lipid accumulation and inflammation through restoring LXRα and PPARα expression and alleviating ER stress in fructose-fed rats—an experiment which indicated that only LXRα participated in ER stress [ 24 ]. Furthermore, Zhao et al confirmed that LXRα degradation is a key factor that induces ER stress stimulated by IFN-γ depending on the PIAS1/STAT1 pathway in macrophages [ 25 ]. However, the detailed mechanism is not fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory response can enhance apoptosis in atherosclerotic lesion macrophages. It was shown that IFN-γ could significantly accelerate STAT1 (signal transducer and activator of transcription protein 1)-dependent degradation of the transcription factor LXRα (liver X receptor α), which can regulate cholesterol efflux by increasing the expression of ABCA1 and ABCG1 under abundance of cellular cholesterol via activation of its polyubiquitination [ 59 ], and upregulate the expression of PERK, eIIF2α, and CHOP proteins, thus contributing to ER stress and enhancing apoptotic processes [ 60 ]. TNFα might also promote ER stress-depended apoptosis in macrophages via activation of UPR pathways [ 61 ].…”
Section: The Role Of Er Stress In Apoptosismentioning
confidence: 99%
“…Pathway-specific responses occur: LXR activation inhibits NF-κB dependent induction of pro-inflammatory genes in response to LPS and responses triggered by TLR4 and TNF-α but exerts minimal impact on the pathway mediated by TLR3[ 86 - 88 ]. LXRs also regulate apoptosis and enhance survival of macrophages within lesions, while IFN-γ promotes neointimal hyperplasia and macrophage apoptosis by promoting ubiquitin-dependent LXR degradation[ 101 , 102 ].…”
Section: Introductionmentioning
confidence: 99%